-6(8-x)+15=-51

Simple and best practice solution for -6(8-x)+15=-51 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(8-x)+15=-51 equation:


Simplifying
-6(8 + -1x) + 15 = -51
(8 * -6 + -1x * -6) + 15 = -51
(-48 + 6x) + 15 = -51

Reorder the terms:
-48 + 15 + 6x = -51

Combine like terms: -48 + 15 = -33
-33 + 6x = -51

Solving
-33 + 6x = -51

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '33' to each side of the equation.
-33 + 33 + 6x = -51 + 33

Combine like terms: -33 + 33 = 0
0 + 6x = -51 + 33
6x = -51 + 33

Combine like terms: -51 + 33 = -18
6x = -18

Divide each side by '6'.
x = -3

Simplifying
x = -3

See similar equations:

| 12-5x=-7x-2 | | 6(x-6)+4=8(x+2)-8 | | 82=2(W+15+W) | | 3x+5-6x=-16 | | 2q^2+4q-1=7q^2-7q+1 | | 2(10-y)=30 | | 10x+6-x=33 | | 5p^2-25=4p^2+24 | | 10+11*h+3=233 | | 2.25=1.5b | | 0.027m*2=0.035m | | 0.027m*2m=0.035+0 | | x^2+9x=-20 | | 3(-1x+4)=-21 | | 3.7g=4.44 | | 5x+24=11-2x | | 6-3x=18x | | 0.027m+2=0.035 | | -0.2(x+1)=0.3(x+111) | | 3x-42=79 | | 0.027+2m=0.035+0 | | 17=33-8x | | x-x+3x+5x=-8x+3x+2+30+5 | | 0.027*2m=0.035+0 | | 2n+20=140 | | (25+12*g)*18=1746 | | -2(7x+9)=-4 | | 2n-10=80 | | -28=-2b | | 2y-4+3(y-7)= | | 4n+12=72 | | x+3x=30 |

Equations solver categories